Size-Dependent Flowering in relation to Grazing in a Short-Lived Monocarpic Perennial - Marco, Diana Elizabeth (2014)
In short-lived monocarpic perennials flowering probability depends on size and relative growth. Reproducing at a smaller size results in a higher prereproductive survival and shorter generation time but also may lead to lower fecundity. Conversely, reproducing at a larger size allows greater fecundity but leads to higher mortality during the prolonged vegetative period. Herbivory may influence the above described relationships via alterations in size at reproduction and survival. Here we use field data to explore in detail the reproduction of the short-lived monocarpic perennial C. vulgare under seasonal grazing. Vegetative plants were marked in paddocks with and without winter grazing, and their size, growth, and flowering status were recorded during a growing season in a field grazing experiment. Grazing increased both survival of vegetative plants and flowering probability, but it did not affect flowering size. The increase in flowering probability is a result of differential plant growth and size and may be related to greater resource availability, including light (necessary for flowering induction in C. vulgare) in grazed paddocks.